Progress report from the AMAP Board to the SAO Meeting in Reykjavik, Iceland, October 23-24, 2003. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2003)
"AMAP is following the approved work plan for the period 2003-2004 as outlined in the SAO report to Ministers, Ivalo 2002. The main task for AMAP during this period is to produce the ACIA scientific assessment and policy reports, to be presented to the Ministerial meeting in 2004. This is a joint work with CAFF and IASC. Prior to the SAO meeting, ACIA will have arranged three important meetings in London (October 7-9 and October 14.-17). A report on the outcome of these meetings will be prepared jointly with CAFF and IASC for delivery to the SAO meeting that takes place the week following the ACIA meetings." /./